Preparation method of bismuth-based up-conversion luminescent glass acidic fluorine removal agent and preparation method and application of photocatalyst

By preparing bismuth-based upconversion luminescent glass acidic fluorine-removing agent, the problems of fluorine ion removal and resource conversion in fluorine-containing wastewater are solved, efficient removal and resource utilization are achieved, and the product has photocatalytic properties.

CN119701925APending Publication Date: 2025-03-28JIANGSU CHANGJILI NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901542.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove fluoride ions in fluorine-containing wastewater and convert them into photocatalytic materials with high added value.

Method used

By preparing a bismuth-based upconversion luminescent glass acidic fluorine-removing agent, bismuth oxide, ytterbium oxide, erbium oxide and silica are mixed in a specific proportion, and after calcination and annealing, it is used to quickly settle fluorine ions in fluorine-containing wastewater and convert them into fluorine-containing semiconductor materials.

Benefits of technology

It realizes efficient removal of fluorine ions in fluorine-containing wastewater and converts them into semiconductor materials with photocatalytic properties, solving the problems of low added value of products and waste of resources in traditional fluorine removal methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701925A_ABST
    Figure CN119701925A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bismuth-based up-conversion luminescent glass acidic fluorine removal agent and a preparation method and application of a photocatalyst, rare earth ions Yb < 3 + > / Er < 3 + > are doped with a Bi2O3-SiO2 matrix, a high-temperature melting method is selected to prepare the bismuth-based up-conversion luminescent glass acidic fluorine removal agent, and the bismuth-based up-conversion luminescent glass acidic fluorine removal agent can effectively remove fluorine ions from fluorine-containing wastewater; the high relative molecular mass of the defluorination product endows the defluorination product with rapid sedimentation capacity, so that a high-purity bismuth-series defluorination product is obtained; and silicon dioxide is introduced into the acidic fluorine removal agent, so that bismuth oxide can be dispersed, agglomeration can be prevented, the loss of bismuth can be greatly reduced in the fluorine removal process, and the stability of the acidic fluorine removal agent serving as a photocatalyst at the rear end is improved. The bismuth-based defluorination product not only retains the excellent up-conversion luminescence characteristic, but also successfully converts fluorine ions into a fluorine-containing semiconductor material. The material can realize efficient photocatalytic degradation activity through up-conversion luminescence under the irradiation of a low-energy light source, and provides a unique function for wastewater treatment and energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a bismuth-based up-conversion luminescent glass acidic defluorinating agent and a method for preparing a photocatalyst and application thereof. Background Art

[0002] Fluoride-containing wastewater mainly comes from the traditional fluoridation industry and the production process using fluoride-containing industrial products. The production of fluoride using natural fluoride-containing minerals as raw materials will produce a large amount of fluoride-containing wastewater. The discharge of these wastewaters leads to a gradual increase in the concentration of fluoride ions (F-) in natural water bodies, posing a serious threat to the ecological environment and human health. At present, commonly used fluoride-containing wastewater treatment technologies include precipitation (chemical / coagulation), adsorption, ion exchange, electrochemistry, and membrane treatment. The core concept of these technologies is to reduce the fluoride ion concentration to below the national emission standard by optimizing the treatment methods, thereby reducing its harm to the ecosystem and humans. At the same time, as fluorine is a non-renewable resource, recycling and utilizing the fluoride resources in its wastewater is also an important goal to achieve resource-based treatment.

[0003] Upconversion luminescent materials are usually composed of inorganic matrix materials and lanthanide rare earth doping ions, and some complexes also have upconversion luminescent properties. Common matrix materials include fluorides, fluoride oxides and oxides. According to the principle of upconversion luminescence, the matrix material plays a vital role in energy transfer and radiationless relaxation. In order to improve the upconversion luminescence efficiency, the matrix material needs to have low phonon energy and a structure suitable for rare earth ion doping. In addition, in order to ensure the stability of the material under complex environments such as high temperature or strong light, the matrix material also needs to have high chemical stability and antioxidant properties. Among them, fluoride oxide (such as BiOF) has become an ideal upconversion luminescent matrix material due to its low phonon energy and good chemical stability. In addition, BiOF also has excellent visible light catalytic performance. In view of this, the present invention provides a method for preparing a bismuth-based upconversion luminescent glass acidic defluorinating agent and a method for preparing and using a photocatalyst. In the present invention, the bismuth-based upconversion luminescent glass generates fluorine-containing semiconductor materials by rapidly settling fluoride ions in fluoride-containing wastewater. These materials not only retain upconversion luminescence properties, but can also be used for photocatalytic degradation of organic pollutants. In this way, not only is the efficient removal of fluorine from fluorine-containing wastewater achieved, but the fluorine resources in the wastewater are also converted into photocatalytic materials with high added value, thus achieving the purpose of resource utilization. Summary of the invention

[0004] The present invention aims to solve the problems existing in the above-mentioned prior art and provides a method for preparing a bismuth-based up-conversion luminescent glass acidic defluorinating agent and a method for preparing a photocatalyst and its application.

[0005] The technical solutions adopted in the present invention are:

[0006] A method for preparing an acidic defluorinating agent for bismuth-based upconversion luminescent glass comprises the following steps: mixing bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide, grinding the mixture, calcining and molding the mixture to obtain bismuth-based upconversion microcrystalline glass; and then annealing the bismuth-based upconversion microcrystalline glass, crushing the mixture and grinding the mixture.

[0007] Furthermore, the mass ratio of bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide is 1:(0.2-0.8):0.05:0.005.

[0008] Furthermore, the calcination temperature is 1100-1500° C., and the calcination time is 10-60 min.

[0009] Furthermore, the annealing treatment conditions are: 300-600° C., 60-120 min.

[0010] The present invention also discloses a photocatalyst, which is based on Bi 3+ With F - The molar ratio of is (0.5-3):1. The bismuth-based up-conversion luminescent glass acidic defluorinating agent prepared by any method according to any one of claims 1 to 4 is mixed with fluorine-containing wastewater for reaction, followed by solid-liquid separation. The obtained defluorinating product can be dried and ground.

[0011] Furthermore, the fluoride ion concentration in the fluoride-containing wastewater is 1-3000 mg / L, and the pH is 0.1-3.

[0012] Furthermore, the reaction time is 2-60 min.

[0013] The invention also discloses the application of the photocatalyst in sewage treatment.

[0014] Furthermore, the application refers to removing organic pollutants in sewage, and the organic pollutants are one or more of toluene, formaldehyde, ciprofloxacin, tetracycline, methyl orange, methylene blue, and rhodamine B.

[0015] Furthermore, the concentration of organic pollutants in sewage is 10-50 mg / L, and the concentration after the photocatalyst is added is 0.1-3 g / L.

[0016] The present invention has the following beneficial effects:

[0017] The present invention converts the rare earth ion Yb 3+ / Er 3+Bi2O3-SiO2 matrix is ​​doped and high-temperature melting method is selected to prepare bismuth-based upconversion luminescent glass acidic defluorinating agent, which can effectively remove fluoride ions from fluoride-containing wastewater, with high defluorination efficiency and large fluoride ion adsorption capacity; the high relative molecular mass of the defluorination product gives it rapid sedimentation ability, avoiding the use of coagulants and pollution of wastewater impurities, thereby obtaining high-purity bismuth-based defluorination products; and the introduction of silicon dioxide in the acidic defluorinating agent can disperse bismuth oxide and prevent agglomeration, and can also greatly reduce the loss of bismuth during the defluorination process, and improve the stability of the back-end as a photocatalyst. The obtained bismuth-based defluorination product not only retains its excellent upconversion luminescence characteristics, but also successfully converts fluoride ions into fluorine-containing semiconductor materials. This material can achieve efficient photocatalytic degradation activity through upconversion luminescence under the irradiation of low-energy light sources (such as visible light and near-infrared light), providing unique functions for wastewater treatment and energy conversion.

[0018] Compared with traditional fluorine removal methods, the present invention can not only efficiently remove fluoride ions, but also convert the fluorine removal products into semiconductor materials with photocatalytic properties. This functional coupling greatly expands the value chain of wastewater treatment, realizes the resource utilization of pollutants, and provides a new path for the comprehensive treatment of fluorine-containing wastewater. The generated fluorine-containing semiconductor material can effectively degrade a variety of organic pollutants, such as dyes, pesticides, and pharmaceutical residues, under ultraviolet or visible light conditions due to its excellent photocatalytic properties. The semiconductor heterojunction inside the material helps to separate photogenerated carriers, improves the photocatalytic efficiency, and thus further enhances the degradation capacity of organic pollutants. The preparation process of the bismuth-based upconversion luminescent glass material in the present invention is green and environmentally friendly, avoiding the secondary pollution problem in the traditional chemical precipitation method. In addition, its rapid sedimentation performance helps to improve the convenience of operation in industrial applications, reduce operating costs, and show broad potential for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The XRD diagrams of the bismuth-based up-conversion luminescent glass acidic defluorinating agents prepared with different raw material ratios in Examples 1-7.

[0020] Figure 2 The fluorine removal efficiency diagram of the bismuth-based up-conversion luminescent glass acidic defluorinating agent prepared with different raw material ratios in Examples 1-7.

[0021] Figure 3 The XRD diagram of the defluorination product in Example 1-7.

[0022] Figure 4 The following are SEM images of the samples in Examples 1-7 before and after defluorination.

[0023] Figure 5 The up-conversion emission spectra of each sample in Examples 1-7 before and after defluorination under 980nm laser.

[0024] Figure 6 The performance diagram of photocatalytic degradation of ciprofloxacin before and after fluorine removal of each sample in Examples 1-7 is shown.

[0025] Figure 7 The performance diagram of photocatalytic degradation of various organic pollutants after fluorine removal of samples of Examples 8-12. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with the accompanying drawings.

[0027] In the following examples, the fluorine-containing solution (F-acidic wastewater) has a pH of 2 under acidic conditions.

[0028] Example 1

[0029] like Figure 1 Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.8:0.05:0.005 and ground thoroughly. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible and preheated to 1100°C in an air atmosphere and kept at 1100°C for 40 minutes. The melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0030] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1 As shown, each sample is labeled GC1.

[0031] The upconversion luminescent glass acid powder GC1 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2 ), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 5 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0032] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the concentration of the photocatalyst was 3 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high pressure mercury lamp. After a certain interval, the solid and liquid were separated and the absorbance of the supernatant was measured on a UV-visible spectrophotometer (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0033] Example 2

[0034] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.7:0.05:0.005 and ground thoroughly. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0035] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1 As shown, the sample is labeled GC2.

[0036] The upconversion luminescent glass acid powder GC2 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2 ), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 6 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0037] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the concentration of the photocatalyst was 2.5 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high-pressure mercury lamp. After a certain interval, the solid and liquid were separated and the supernatant was measured on a UV-visible spectrophotometer to determine the absorbance (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0038] Example 3

[0039] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.6:0.05:0.005 and ground thoroughly. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0040] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1 As shown, the sample is labeled GC3.

[0041] The upconversion luminescent glass acid powder GC3 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2 ), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 6 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0042] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the concentration of the photocatalyst was 1.5 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high-pressure mercury lamp. After a certain interval, the solid and liquid were separated and the supernatant was measured on a UV-visible spectrophotometer to determine the absorbance (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0043] Example 4

[0044] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.5:0.05:0.005 and fully ground. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0045] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1As shown, the sample is labeled GC4.

[0046] The upconversion luminescent glass acid powder GC4 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2 ), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 6 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0047] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the concentration of the photocatalyst was 1.2 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high-pressure mercury lamp. After a certain interval, the solid and liquid were separated and the supernatant was measured on a UV-visible spectrophotometer to determine the absorbance (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0048] Example 5

[0049] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.4:0.05:0.005 and ground thoroughly. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0050] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1 As shown, the sample is labeled GC5.

[0051] The upconversion luminescent glass acid powder GC5 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 6 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0052] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the photocatalyst concentration was 1 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high pressure mercury lamp. After a certain interval, the solid and liquid were separated and the absorbance of the supernatant was measured on a UV-visible spectrophotometer (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0053] Example 6

[0054] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.3:0.05:0.005 and ground thoroughly. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0055] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1 As shown, the sample is labeled GC6.

[0056] The upconversion luminescent glass acid powder GC6 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2 ), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 6 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0057] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the photocatalyst concentration was 0.8 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high-pressure mercury lamp. After a certain interval, the solid and liquid were separated and the supernatant was measured on a UV-visible spectrophotometer to determine the absorbance (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0058] Example 7

[0059] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.2:0.05:0.005 and fully ground. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0060] The obtained upconversion glass-ceramics was annealed at 200°C for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Its XRD is as follows: Figure 1 As shown, the sample is labeled GC7.

[0061] The upconversion luminescent glass acid powder GC7 was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio, stirred at room temperature for 60 min, and then separated into solid and liquid (F - The removal efficiency is shown in Figure 2 ), the defluorination product after 60 minutes is dried and ground to obtain the defluorination product photocatalyst (the XRD diagram and luminescence performance diagram of the defluorination product photocatalyst are shown in Figure 3 , 6 The SEM images of the upconversion luminescent glass acid powder before and after defluorination are shown in Figure 4 shown).

[0062] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the photocatalyst concentration was 0.1 g / L and pH = 7, and stirred for 2 h in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high pressure mercury lamp. After a certain interval, the solid and liquid were separated and the supernatant was measured on a UV-visible spectrophotometer to determine the absorbance (the degradation efficiency of ciprofloxacin is shown in Figure 6 ).

[0063] Comparative Example 1

[0064] Silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.05:0.005 and fully ground. The resulting raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1100°C in an air atmosphere, and kept at 1100°C for 40 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based up-conversion glass-ceramics.

[0065] The obtained upconversion glass-ceramics are annealed at 200° C. for 120 min, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Each sample is marked as GC.

[0066] The up-conversion luminescent glass acid powder GC was mixed with 1000 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =1:1 ratio and then stirred at room temperature for 60 minutes, and then the solid-liquid separation was carried out. The defluorination product after 60 minutes was dried and ground to obtain the defluorination product photocatalyst.

[0067] Due to the lack of bismuth, fluoride oxide cannot be produced to precipitate fluoride ions, making the prepared upconversion luminescent glass powder GC and 1000mg·L -1 F - After solid-liquid separation of the solution reaction, the fluoride ion concentration in the supernatant does not change much, so there is almost no fluoride removal efficiency.

[0068] Example 8

[0069] The method of this embodiment is the same as that of embodiment 1, except that the organic pollutant is methanol, denoted as GC8. Figure 7 .

[0070] Example 9

[0071] The method of this embodiment is the same as that of embodiment 1, except that the organic pollutant is formaldehyde, denoted as GC9. Figure 7 .

[0072] Example 10

[0073] The method of this embodiment is the same as that of embodiment 1, except that the organic pollutant is tetracycline, denoted as GC10. Figure 7 .

[0074] Embodiment 11

[0075] The method of this embodiment is the same as that of embodiment 1, except that the organic pollutant is methyl orange, denoted as GC11. Figure 7 .

[0076] Example 12

[0077] The method of this embodiment is the same as that of embodiment 1, except that the organic pollutant is methylene blue, denoted as GC12. Figure 7 .

[0078] Embodiment 13

[0079] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.7:0.05:0.005 and fully ground. The obtained raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1500°C in an air atmosphere, and kept at 1500°C for 10 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0080] The obtained upconversion glass-ceramics are annealed at 100°C for 60 minutes, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Each sample is marked as GC13.

[0081] The upconversion luminescent glass acid powder GC13 was mixed with 1 mg·L -1 F - Acidic wastewater according to Bi 3+ :F - =0.5:1 ratio at room temperature and then stirred for 2, 30, and 60 minutes, and then the solid-liquid separation was carried out. The defluorination product after 60 minutes was dried and ground to obtain the defluorination product photocatalyst.

[0082] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the photocatalyst concentration was 2.7 g / L and pH = 5, and stirred for 1 hour in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high-pressure mercury lamp. After a certain interval, the solid-liquid separation was performed and the absorbance of the supernatant was measured on a UV-visible spectrophotometer.

[0083] Embodiment 14

[0084] Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed in a mass ratio of 1:0.7:0.05:0.005 and fully ground. The resulting raw material mixture (total mass 20 g) is placed in a corundum crucible, preheated to 1500°C in an air atmosphere, and kept at 1500°C for 60 minutes; the melt is quickly poured onto a steel plate at high temperature to obtain bulk bismuth-based upconversion glass-ceramics.

[0085] The obtained upconversion glass-ceramics were annealed at 500°C for 90 minutes, and then crushed and fully ground to obtain upconversion luminescent glass acidic defluorinating agent powder. Each sample was marked as GC14.

[0086] The upconversion luminescent glass acid powder GC14 was mixed with 3000 mg·L -1 F - Acidic wastewater Bi 3+ :F - =3:1 ratio at room temperature and then stirred for 2, 30, and 60 minutes, and then the solid-liquid separation was carried out. The defluorination product after 60 minutes was dried and ground to obtain the defluorination product photocatalyst.

[0087] The photocatalyst was added to 20 mL of 10 mg / L ciprofloxacin solution until the photocatalyst concentration was 2.9 g / L and pH = 8, and stirred for 3 hours in the dark to achieve adsorption and desorption equilibrium, and then irradiated with a 1000 W high-pressure mercury lamp. After a certain interval, the solid-liquid separation was performed and the supernatant was taken to measure the absorbance rate on a UV-visible spectrophotometer.

[0088] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a bismuth-based upconversion luminescent glass acidic defluorinating agent, characterized in that: Bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide are mixed and ground, calcined and formed to obtain bismuth-based upconversion glass-ceramics; the bismuth-based upconversion glass-ceramics are annealed, crushed and ground.

2. The method for preparing the bismuth-based up-conversion luminescent glass acidic defluorinating agent according to claim 1, characterized in that: The mass ratio of bismuth oxide, silicon dioxide, ytterbium oxide and erbium oxide is 1:(0.2-0.8):0.05:0.

005.

3. The method for preparing the bismuth-based up-conversion luminescent glass acidic defluorinating agent according to claim 1, characterized in that: The calcination temperature is 1100-1500°C, and the calcination time is 10-60min.

4. The method for preparing the bismuth-based up-conversion luminescent glass acidic defluorinating agent according to claim 1, characterized in that: The annealing conditions are: 300-600°C, 60-120min.

5. A photocatalyst, characterized in that: According to Bi 3+ With F - The molar ratio of is (0.5-3):

1. The bismuth-based up-conversion luminescent glass acidic defluorinating agent prepared by any method according to any one of claims 1 to 4 is mixed with fluorine-containing wastewater for reaction, followed by solid-liquid separation. The obtained defluorinating product can be dried and ground.

6. The photocatalyst according to claim 5, characterized in that: The fluoride ion concentration in fluoride-containing wastewater is 1-3000 mg / L and the pH is 0.1-3.

7. The photocatalyst according to claim 5, characterized in that: The reaction time is 2-60min.

8. Use of the photocatalyst according to any one of claims 5 to 7 in sewage treatment.

9. The use according to claim 8, characterized in that The application refers to removing organic pollutants in sewage, and the organic pollutants are one or more of toluene, formaldehyde, ciprofloxacin, tetracycline, methyl orange, methylene blue, and rhodamine B.

10. The use according to claim 8, characterized in that: The concentration of organic pollutants in sewage is 10-50 mg / L, and the concentration after the addition of photocatalyst is 0.1-3 g / L.